Lesion-symptom mapping of language impairments in patients suffering from left perisylvian gliomas. (November 2021) - Fekonja, Lucius S.; Wang, Ziqian; Doppelbauer, Lea; Vajkoczy, Peter; Picht, Thomas; Pulvermüller, Friedemann; Dreyer, Felix R.
Abstract: Brain tumors cause local structural impairments of the cerebral network. Moreover, brain tumors can also affect functional brain networks more distant from the lesion. In this study, we analyzed the impact of glioma WHO grade II-IV tumors on grey and white matter in relation to impaired language function. In a retrospective analysis of 60 patients, 14 aphasic and 46 non-aphasic, voxel-based lesion-symptom mapping (VLSM) was used to identify tumor induced lesions in grey (GM) and white matter (WM) related to patients' performance in subtests of the Aachen Aphasia Test (AAT). Significant clusters were analyzed for atlas-based grey and white matter involvements in relation to different linguistic modalities. VLSM analysis indicated significant contribution of a posterior perisylvian cluster covering WM and GM to AAT performance averaged across subtests. When considering individual AAT subtests, a substantial overlap between significant clusters for analysis of the token test, picture naming and language comprehension results could be observed. The WM-cluster intersections reflect the overall importance of the perisylvian area in language function, similarly to GM participations. Especially the constant high percentages of Heschl's gyrus, superior temporal gyrus, inferior longitudinal and middle longitudinal fascicles, but also arcuate and inferior fronto-occipital fascicles highlight the importance of the posterior perisylvian area for language function.